Screening common bean accessions for resistance to charcoal rot (Macrophomina phaseolina) in Eastern Kenya - Songa, WA; Hillocks, RJ; Mwang’ombe, A.W.; Buruchara, Robin Arani; Ronno, WK (1997)
Common bean (Phaseolus vulgaris L.) germplasm was screened for resistance to charcoal rot (Macrophomina phaseolina) under field conditions at Kiboko and Katumani, eastern Kenya. Of the 313 bean accessions evaluated, 50 lines were resistant and six were tolerant to M. phaseolina, the charcoal rot incidence was less than 25% and between 25% and 50% for the resistant and tolerant lines respectively. Yields ranged from 135 to 1051 kg ha?1 compared with 55 kg for the susceptible control A464. Time to maturity did not seem to influence or affect the susceptibility or resistance to M. phaseolina of the various bean accessions.